2013
DOI: 10.1370/afm.1478
|View full text |Cite
|
Sign up to set email alerts
|

Medical Home Transformation: A Gradual Process and a Continuum of Attainment

Abstract: PURPOSEThe patient-centered medical home is often discussed as though there exist either traditional practices or medical homes, with marked differences between them. We analyzed data from an evaluation of certifi ed medical homes in Minnesota to study this topic. METHODSWe obtained publicly reported composite measures for quality of care outcomes pertaining to diabetes and vascular disease for all clinics in Minnesota from 2008 to 2010. The extent of and change in practice systems over that same time period f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…9,17,20,25,26 A survey of medical home implementation in 65 safety-net clinics found that greater implementation of characteristics of the medical home was associated with both higher morale and higher provider burnout. 27 This finding is consistent with the context we encountered, where many participants described PACT implementation as both exciting and stressful.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,20,25,26 A survey of medical home implementation in 65 safety-net clinics found that greater implementation of characteristics of the medical home was associated with both higher morale and higher provider burnout. 27 This finding is consistent with the context we encountered, where many participants described PACT implementation as both exciting and stressful.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated in a previous publication that this practice systems measure is associated with changes in performance measures for patients with diabetes or cardiovascular disease. 21 Many of the items in Tables 2 and 3 were suggested as important by others, usually based on expert opinion. In fact, some of them (patient engagement, care coordinator job description, focus on care plans, use of formal quality improvement techniques) are required by the certification process in Minnesota.…”
Section: Discussionmentioning
confidence: 99%
“…Their performance on quality measures may vary within the group of certified practices, but, on average, it is significantly higher than the average for noncertified clinics (although it was also higher 3 years before being certified. 35 Therefore, it is possible that these higher-performing clinics chose to be certified based on a longstanding goal of being leaders, with recognition and payment as collateral goals, rather than because the certification process documented the improvement. Only time will tell whether certification leads to an increase in their lead over noncertified clinics.…”
Section: Discussionmentioning
confidence: 99%
“…3 Research evaluating the PCMH's effectiveness in achieving the goals of improved care quality, patient experience, and reduced healthcare costs has encouraged further refinement of the model. [4][5][6][7][8][9][10][11] Facilitators and barriers to the creation of a successful PCMH have been explored in a limited number of heterogeneous settings, including small practices, large group practices, high-performing practices, and safety net clinics. [12][13][14][15][16][17] To date, significant challenges have been identified; specifically, the investment of resources for infrastructure changes and the leadership skills needed to guide an organization through paradigm-shifting cultural change.…”
Section: Introductionmentioning
confidence: 99%